Low-carbon economic dispatch of integrated energy system considering carbon trading and integrated demand response with CCER. Issue 1 (1st December 2022) - Wei, Nan; Jia, Yanbing; Tao, Hongfei; Yan, Zhikun; Chen, Junxian
Abstract: Under the background of 'double carbon, ' to promote the transformation of generating units to new energy power generation in an integrated energy system and better realize carbon trading functions, the paper gives a carbon trading model considering CCER and a low carbon economy scheduling model considering joint demand response. First, consider the nationally certified voluntary emission reductions for wind power applications in the traditional carbon trading model, and improve the benefit of investment in renewable energy projects to strengthen the conversion of traditional energy structures to new energy structures while reducing the amount of carbon emissions in the system. Second, price-based and alternative responses are introduced on the user demand side to accurately model and optimize the load curve. The model is solved by using the CPLEX solution toolbox, and the correctness of the given model is proved by simulation.